"Philology and criticism: the Pavia school and Ricciardi's house of publishing". Review of the proceedings of Bergamo Conference, 'Angelo Mai' Library, 21 May 2016 (Prassi Ecdotiche della Modernità Letteraria, 2017)
On May 21st 2016, the sixth day of studies in honor of Franco Gavazzeni, promoted by Rosanna Paccanelli and by the children Giulia and Michele, took place in Bergamo, in the newly restored Salone Furietti of Angelo Mai Library. Since a happy coincidence has wanted that in those days was recurring the ninetieth birthday of one of Gavazzeni's dearest friends, Gianni Antonini, the soul of Ricciardi publishing house, spontaneously offered to the promoters of the initiative the theme of that day: the relationships between Ricciardi publishing house and Pavia philological school. A precious small book collects, thanks to the care of Sara Rosini, the results.
Keywords: philology; criticism; Pavia; Franco Gavazzeni; Gianni Antonini; Ricciardi publishing house